Plan de implementación de un sistema integrado de gestión de calidad y ambiental en una empresa del sector siderúrgico (2016)
This paper presents the case study in which an organization approves the evaluation of its processes and activities to determine the relevance and viability of the implementation of an integrated management system ISO 9001: 2015 and ISO 14001: 2015. To fulfill the fundamental objective, the study is divided into three stages with which the proposal of a specific implementation plan for the company is carried out.